Prognostic impact of interval breast cancer detection in women with pT1a N0M0 breast cancer with HER2-positive status: Results from a multicentre population-based cancer registry study. (January 2018) - Musolino, A.; Falcini, F.; Sikokis, A.; Boggiani, D.; Rimanti, A.; Pellegrino, B.; Silini, E.M.; Campanini, N.; Barbieri, E.; Zamagni, C.; Degli Esposti, R.; Cortesi, L.; et al.
Abstract: Background: Although human epidermal growth factor receptor 2 (HER2) overexpression is associated with poor prognosis, patients (pts) with pT1a N0M0 breast cancers (BCs) have an excellent outcome across all subtypes. Interval cancers (ICs) have poorer survival than screen-detected (SD) tumours, and an association has been reported between ICs and HER2 overexpression. We aimed to determine, in a general population of pT1a N0M0 BCs with known screening status, whether HER2-positive ICs have a poorer outcome than HER2-positive SD cancers. Methods: We evaluated all incident pT1a N0M0 BCs (n = 874) collected in the Emilia-Romagna region (Italy) from 2003 to 2009 and diagnosed in women aged 50–69. Pts unexposed to screening, with unknown HER2 status and/or treated with adjuvant trastuzumab were excluded from analysis. Results: Sixty-one percent of the BCs were SD, whereas 19% were ICs. BCs with high histologic grade, hormone receptor–negative or HER2-positive status (odds ratio = 1.7; 95% confidence interval [CI]: 1.1–2.7) were more likely ICs. Median follow-up was 115 months. The 10-year invasive disease-free survival (iDFS) for HER2-positive ICs was lower than that for HER2-positive SD cancers: 75.0% (95% CI: 55.5%–94.5%) versus 93.8% (95% CI: 86.5%–100%). An interaction between ICs and HER2-positive status was found for poorer iDFS after adjusting for prognostic variables (HR = 5.3; 95% CI: 1.6–16.7). Conclusions: IC detection may identify pts with HER2-positive pT1a N0M0 tumours in whom the rate of recurrence justifies consideration for conventional, anti-HER2, adjuvant treatment. Highlights: pT1a N0M0 human epidermal growth factor receptor 2 (HER2)-positive interval cancers have a poorer outcome than HER2-positive screen-detected (SD) cancers. Consider aggressive adjuvant treatments only in patients with interval-detected tumours. Avoid overtreatment strategies in small, HER2-positive SD cancers.